Tesoros simbólicos. Imágenes sagradas en los monasterios femeninos de las ciudades virreinales novohispanas - Rubial García, Antonio (2013)
Drawn from examples principally of the seventeenth and eighteenth centuries, this article analyzes the importance which feminine monasteries enjoyed in the cities of New Spain because they administered religious images which were considered miraculous. The images attracted numerous faithful, which resulted in increased economic benefits for the monasteries, thanks to the alms, and the social prestige of the monasteries. Finally, the article argues that, for the cities which housed these monasteries, the presence of the nuns who administered the images was fundamental for constructing their local identity.